EFISIENSI UNIT-UNIT KEGIATAN EKONOMI INDUSTRI GULA YANG MENGGUNAKAN PROSES KARBONATASI DI INDONESIA - VICTOR SIAGIAN (SOCA: Jurnal Sosial Ekonomi Pertanian)
Highly government intervention caused crucial Indonesian sugar market structure.This condition stimulated low productivity, high cost economy, increasing in sugar price andimported sugar. Increased sugar import either legal or illegal must be concerned becauseinternational sugar market is thin market and also sugar industry is capital intensive, moreover in the beginning of trade liberalization. One of the methods for eliminating importedsugar namely to identified sugar industry efficiency especially carbonatization sugar industryusing Data Envelopment Analysis (DEA).DEA calculates relative efficiency to peer unit namely sugar factories in which havehighly efficiency score. There are three sugar factories, using carbonatization process, havelowly efficiency score and need input multiplier or reallocation in using input from peer unit.